On the derivation of graphically inspired feasibility constraints for distillation network synthesis - Ryu, Joonjae; Maravelias, Christos T. (AIChE journal, 2022)
We propose the integration of simplified graphically inspired feasibility constraints into optimization‐based models for distillation network synthesis. The approach facilitates the use of surrogate, potentially data‐based, distillation column models while considering feasibility in a computationally efficient manner. The proposed approach can aid the formulation of efficient approaches for preliminary distillation network synthesis.